PROBLEM SOLVING ANALYSIS OF PEOPLE'S BUSINESS CREDIT FINANCING BASED ON MURABAHAH AGREEMENT AT PT. BANK SYARIAH INDONESIA TBK. MAGELANG SINGOSARI SUB-BRANCH OFFICE - Andi Faisal Ridho; Chaidir Iswanaji; Suci Nasehati Sunaningsih (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2022)
This study aims to determine the resolution of murabahah contract problems related to the factors that influence the micro-financing of the People's Business Credit (KUR) carried out by the financial institution PT Bank Syariah Indonesia Tbk., Magelang Singosari Sub-Branch Office in channeling People's Business Credit (KUR) funds. The method used in this study is descriptive qualitative and data analysis used in this study uses primary and secondary data. The results of the analysis of customer funding of Bank BSI Magelang Singosari Sub-Branch Office are inseparable from the factors and risks. One of them is bad money, which causes a decrease in bank liquidity and affects the reliability of customer savings. In the case of non-performing loans, banks must analyze the factors that affect bank liquidity so as not to cause losses and provide an analysis of bad credit settlement through time relief and installment assistance, especially if the creditor is affected by a disaster, if it is not paid on purpose, it will be confiscated.